Cervical cancer survivors' attitudes and understanding of menopause and hormone therapy. Issue 6 (June 2020) - Cotangco, Katherine; Class, Quetzal A.; Johnson, Timothy P.; Kothari, Rajul
Abstract: Objective: We designed a survey study to assess the presence and severity of climacteric symptoms, in addition to better understand patients' knowledge and understanding of hormone therapy (HT). Methods: We administered a 23-question survey during a patient's clinic visit or over the phone. Study enrollment spanned from March, 2019 to May, 2019. The primary outcomes were severity of menopausal symptoms and willingness to try HT, calculated as a summarized overall score. Chi-square and logistic regression were used for analysis. Results: Our response rate was 38% (n = 34). Our participants were diverse—67% women were black and 21% women were Hispanic. Stage 1 and 2 disease was reported in 32% and 41% of women. Also, 82% and 94% of women reported ever receiving any chemotherapy or radiation therapy. There was no association between willingness to try HT for relief of menopausal symptoms and income (χ 2 [1, 29] = 0.56, P  = 0.81) or education level (χ 2 [1, 29] = 2.78, P  = 0.10). The most common climacteric symptoms experienced were hot flushes (85%) and decreased libido (77%). Neither symptom severity (odds ratio [OR] 1.31, 95% confidence interval [CI] 0.89-1.94) nor concern for side effects (OR 1.06, 95% CI 0.82-1.36) of HT significantly predicted willingness to try HT. Conclusions: Menopausal symptoms were prevalent in this population. Our data indicate that women are experiencing climacteric symptoms, but are overall unmotivated to address symptoms using HT. Factors such as symptom severity, fear of side effects, income level, or education level were not associated with acceptability of HT for premature menopause.